Factors Influencing the Resilience of Created Tidal Marshes in the Fraser River Estuary, British Columbia - Daniel Stewart; Megan Lievesley; James E. Paterson; Daniel Hennigar; Robyn Ingham; Rob Knight; Brad Mason; Eric Balke (Wetlands, 2024)
More than 100 tidal marsh creation projects were constructed throughout the Fraser River Estuary, British Columbia, Canada from the 1980s to present. Past studies described and evaluated many of these projects and found varied success, but the underlying factors that determine project outcomes remain uncertain. Combining field sampling, spatial analysis, and statistical modeling of plant communities, we aim to address this knowledge gap by asking what factors influence the resilience of created marshes, as measured by (1) persistence of marsh vegetation, (2) native species dominance, and (3) species richness. We observed marsh recession in 40 of the 78 projects visited, representing 23,666 m 2 (9.3%) of the 254,357 m 2 of created marsh surveyed. Increases in mean site elevation had a negative effect on percent recessed area, while sites in the north branch of the river and sites further upriver were more prone to recession. From field observations and data interpretation we suggest that wake erosion and Canada Goose ( Branta canadensis ) herbivory may be drivers behind these losses and warrant further investigation. Dominance of native species declined with distance upriver, though invasive cattail ( Typha angustifolia, T. × glauca) defied this trend, dominating outer estuary sites, particularly closed embayments, when present. Native and non-native richness shared similar patterns and were comparable between reference and created marshes, increasing on average with elevation and distance upriver. These findings offer insight into how site design and location influence the outcome of marsh creation projects, and the challenges presented by stressors and environmental change in estuaries.